DOI Sosialisasi dan Pendampingan Artificial Intelligence Berbasis Partisipatif sebagai Upaya Penguatan Pendidikan Kreatif Siswa - Nanda Sahita; Mambaul Chiqmah; Yogi Ardiansyah; Huan Aji Kusni; Yusuf Putra Pratama; Muhammad Azam Dhiyauz Zaman (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
The utilization of Artificial Intelligence (AI) in the field of design has become an urgent need in vocational education, particularly for students of Vocational High Schools (SMK) majoring in Visual Communication Design (DKV), in response to the demands of the creative industry that emphasize efficiency, technological adaptability, and work readiness. The main problem identified is the limited understanding and skills of students in using AI productively and ethically within the design process, both among Grade XI students who are preparing for internships and Grade X students studying Informatics. This activity aims to introduce fundamental concepts, potential applications, and practical uses of AI in graphic design in a contextual manner aligned with industry needs. The implementation method consisted of four stages: socialization, training, evaluation, and follow-up. The results indicate a high level of student enthusiasm, as reflected in active participation and the emergence of critical questions regarding creativity, originality of works, and the impact of AI on future career prospects in the creative industry. Hands-on practice proved particularly beneficial for Grade XI students by improving efficiency and timeliness in completing design tasks as preparation for internships. This activity concludes that the introduction of AI accompanied by applied practice can enhance technological literacy, job-related skills, and students’ critical thinking in facing collaboration between humans and technology in the creative industry.